2D nanocrystalline ternary selenides Cu2MSe4 (M = Mo/W). Issue 42 (16th October 2019) - Li, Minyuan M.; Ivanov, Sergei A.
Abstract : A high-temperature metathesis reaction between CuBr and [Ph4 P]2 MSe4 (M = Mo or W) gave rise to nanocrystalline Cu2 MSe4 with a phase-pure M = Mo compound that was obtained for the first time. Abstract : A high-temperature metathesis reaction between CuBr and [Ph4 P]2 MSe4 (M = Mo or W) gave rise to nanocrystalline Cu2 MSe4 with a phase-pure M = Mo compound that was obtained for the first time. After exploring the formation mechanism, we found that the sub-stoichiometric ratios of CuBr to MSe4 2− resulted in the formation of a linear byproduct impurity, [Ph4 P]CuMSe4 (M = Mo or W). However, excess CuBr selectively steered the reaction to the desired Cu2 MSe4 . As a consequence of the newfound similarity in the reaction conditions for both metals, we have demonstrated the applicability of this method towards a mixed Mo/W quaternary composition.